The Impact of Green Supply Chain Management Practices on Company Performance in the Cafe Industry in Cimahi City - Alya Rahmawati; Asep Kurniawan (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
Increasing environmental challenges and rising waste production have prompted businesses to adopt environmentally friendly and sustainable practices. The café industry, which is experiencing rapid growth in Indonesia particularly in the city of Cimahi contributes to environmental problems through the use of plastic packaging, single-use products, and operational waste. Consequently, the Using Green Supply Chain Management (GSCM) techniques has become increasingly important to support business sustainability and improve company performance. The purpose of this study is to investigate how corporate performance is affected by green supply chain management methods, which are exemplified by eco-design, green manufacturing, and green purchasing in cafes in Cimahi City. This study employs a quantitative approach using descriptive and associative analyses. Primary data were collected from 66 respondents comprising café owners and employees—via a questionnaire. Simple random sampling was used, and SPSS version 25 was used to do multiple regression analysis on the data. The outcomes show that respondents’ perceptions of eco-design, green manufacturing, green purchasing, and overall company performance were generally categorized as moderate. At the same time, eco-design, the performance of businesses is significantly impacted by green manufacturing and green purchasing. However, when analyzed individually, eco-design does not significantly impact company performance, whereas in Cimahi City's cafés, green manufacturing and green purchasing have favorable and substantial benefits.